The Quest for CSR in Closedowns - Alexis Rydell; Rune Wigblad (Nordic Journal of Working Life Studies, 2012)
This paper focuses on analysis of and suggestions for Corporate Social Responsibility (CSR) orientation during the closedown process. The article addresses CSR considerations that adjust business strategies, which in turn change the Human Resource Management (HRM) focus. Our study focuses on four best practice cases in Sweden, which are compared with three reported cases in the literature. All four best practice cases had a long notice period and socially responsible coordination of management and employees, which created adjusted corporate strategies. Three cases had the CSR orientation in the earliest stage, while the fourth case had this coordination during a later stage of the closedown process. We develop a model where we show that the scope for action increases if the CSR orientation and coordination of actions come early in the closedown process, due to the increased ability to adjust the business strategy and create a plan for outreach HRM activities and local community activities.